THE CLINICAL FEATURES AND PROGNOSTIC VALUE OF INFLAMMATORY POLYPS IN THE J POUCH OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE TREATED BY PROCTOCOLECTOMY WITH ILEAL POUCH-ANAL ANASTOMOSIS. (21st January 2021) - Akiyama, Shintaro; Ollech, Jacob; Rai, Victoria; Yi, Yangtian; Traboulsi, Cindy; Glick, Laura; Runde, Joseph; Cohen, Russell; Hurst, Roger; Hyman, Neil; Dalal, Sushila; Sakuraba, Atsushi; et al.
Abstract: Background: Patients with inflammatory bowel disease (IBD) sometimes require proctocolectomy with ileal pouch-anal anastomosis (IPAA) due to medically refractory colitis or neoplasia. However, pouchitis can develop in up to 80% of patients after the surgery. Given that previous studies demonstrated an association between chronic pouchitis and inflammatory polyps, we hypothesize that inflammatory polyps can be a predictor for pouch outcomes. This study assesses the frequency, risk factors, and prognosis of the J pouch with inflammatory polyps. Methods: This is a retrospective single-center study of IBD patients treated by total proctocolectomy with IPAA and who subsequently underwent pouchoscopies at the University of Chicago between January 2007 and September 2019. We reviewed the endoscopic findings in different anatomic areas of the pouch: the pre-pouch ileum, inlet, "tip of the J", proximal and distal pouch, anastomosis, rectal cuff, anal canal, and perianal area. Endoscopic findings included erythema/edema, erosions/friability, ulcerations, stenosis, granularity, loss of vascular pattern, and inflammatory polyps. To compare the J pouch with and without inflammatory polyps, we evaluated all available pouchoscopies and included any patient who had inflammatory polyps noted at least once. Demographic and clinical data were also assessed. Fisher's test was used for a univariate analysis to assess factors contributing to inflammatory polyps in the J pouch. Logistic regression analysis was performed by including univariate variables with a P-value < 0.05. To assess the relevance between inflammatory polyps and pouch excision, log-rank test and Kaplan-Meier curve were used. Results: We reviewed 1, 195 pouchoscopies from 426 IBD patients who underwent proctocolectomy with IPAA and identified 61 patients (14.3%) with at least 1 inflammatory polyp in the J pouch. The most common anatomical location developing inflammatory polyps was the distal pouch (23, 38%), followed by the proximal pouch (21, 34%), afferent limb (13, 21%), rectal cuff (9, 15%), and inlet (7, 11%). Multivariable analysis showed that inflammatory polyps were significantly associated with male sex (OR = 2.8; 95% CI = 1.4–5.3; P = 0.002), postoperative anti-TNF drugs (OR = 2.9; 95% CI = 1.6–5.4; P < 0.001), and pouchitis (OR = 6.1; 95% CI = 1.4–25.9; P = 0.015) (Table). Kaplan-Meier curve showed that inflammatory polyps significantly increased the risk of pouch excision (P = 0.03) (Figure 1). Conclusion: Our analysis found that more than 10% of IBD patients with a J pouch developed inflammatory polyps. Male patients had an increased risk of inflammatory polyps in the J pouch. Furthermore, our study suggested that inflammatory polyps can develop in patients with pouchitis requiring anti-TNF drugs and are an independent predictor of pouch excision. Table Figure 1